2023
DOI: 10.4070/kcj.2022.0301
|View full text |Cite
|
Sign up to set email alerts
|

LOXL1-AS1 Aggravates Myocardial Ischemia/Reperfusion Injury Through the miR-761/PTEN Axis

Abstract: Author's summary Lysyl oxidase like 1 antisense RNA 1 (LOXL1-AS1) promoted hypoxia/reoxygenation (H/R)-induced pyroptosis in cardiomyocyte. MiR-761 inhibited H/R-induced pyroptosis in cardiomyocyte. LOXL1-AS1 targeted miR-761 and miR-761 targeted phosphatase and tensin homolog. LOXL1-AS1 induced cardiomyocyte pyroptosis by targeting miR-761 under H/R conditions. LOXL1-AS1 enhanced myocardial ischemia and reperfusion injury in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Another study, in which cardiac ischemia reperfusion was searched, reported that mTOR and Akt values in I/R group were found higher than that of the sham group (28). He et al (29) found that PTEN was highly expressed after I/R when they studied on human cardiomyocyte. In our study, PTEN, Akt and mTOR levels showed the significant difference between groups but not PI3K level (P>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Another study, in which cardiac ischemia reperfusion was searched, reported that mTOR and Akt values in I/R group were found higher than that of the sham group (28). He et al (29) found that PTEN was highly expressed after I/R when they studied on human cardiomyocyte. In our study, PTEN, Akt and mTOR levels showed the significant difference between groups but not PI3K level (P>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…First, the authors confirmed that LOXL1-AS1 was highly expressed under hypoxia/reoxygenation conditions. 10) This increased LOXL1-AS1 negatively regulated miR-761 level the as a molecular sponge. In addition, the authors also confirmed that miR-761 downregulates the mRNA level of PTEN.…”
mentioning
confidence: 97%
“…In this issue of the Korean Circulation Journal , He et al 10) investigated the LOXL1-AS1 play a key epigenetic regulator in cardiomyocyte pyroptosis in MIRI. The authors proposed LOXL1-AS1/miR-761/PTEN as a novel signaling pathway affecting pyroptosis in MIRI.…”
mentioning
confidence: 99%
See 2 more Smart Citations